Intrathecal Morphine and Oral Analgesics Provide Safe and Effective Pain Control After Posterior Spinal Fusion for Adolescent Idiopathic Scoliosis. Issue 2 (15th January 2018) - Li, Ying; Hong, Rebecca A.; Robbins, Christopher B.; Gibbons, Kathleen M.; Holman, Ashlee E.; Caird, Michelle S.; Farley, Frances A.; Abbott, Matthew D.; Burke, Michelle C.
Abstract : Study Design: Retrospective comparative study. Objective: The aim of this study was to demonstrate that intrathecal morphine (ITM) and oral analgesics provide effective pain control after posterior spinal fusion (PSF) for adolescent idiopathic scoliosis (AIS), and this protocol has a low complication rate so patients can be admitted to a general care floor. Summary of Background Data: Previous studies have shown that ITM combined with intravenous patient-controlled analgesia or epidural infusion (EPI) provides effective pain control after PSF for AIS. Owing to concerns for respiratory depression, ITM patients were routinely admitted to the intensive care unit (ICU) postoperatively. There are little data on ITM combined with oral analgesics. Methods: We identified AIS patients aged 10 to 17 years who had undergone PSF. Twenty-eight patients who received ITM were matched to 28 patients who received a hydromorphone EPI. The ITM group received oral oxycodone starting at 16 hours postinjection. The EPI group received oxycodone after the epidural catheter was removed on postoperative day 2. Pain scores, adverse events, and length of stay were recorded. Results: A higher number of EPI patients received fentanyl (11 vs. 3, P = 0.014) in the post-anesthesia care unit (PACU). The ITM group had lower pain scores between PACU discharge and midnight (mean 2.9 vs. 4.2, P = 0.034). Pain scores were similar during the remaining postoperative periods. All ITM patients transitioned to oxycodone without intravenous opioids. Time to ambulation (19.9 vs. 26.5 hours, P = 0.010) and Foley catheter removal (21.3 vs. 41.9 hours, P < 0.001) were earlier in the ITM patients. Length of hospital stay was shorter in the ITM group (3.1 vs. 3.5 days, P = 0.043). Adverse events occurred at similar rates in both groups. Conclusion: ITM and oral analgesics provide safe and effective pain control after PSF for AIS. Routine postoperative admission to the ICU is not necessary. Level of Evidence: 3